STUDENT'S PERCEPTION ON THE ACTIVITIES PLACES DURING COVID-19 PANDEMIC - Luru, Marselinus Nirwan; Rahel Situmorang; Dewi Setiani; Farah Fauziah Andini (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2021)
Research on the impact of the COVID-19 pandemic on human activities has produced many new findings. This research is built on the basis of changes in the culture of student activities, which are mostly carried out offline towards a new culture in online activities. This study examines the changes in the types of activities, the place of activities and the pattern of student activities. Through quantitative research methods, data acquisition through questionnaires and descriptive analysis, found that students' weekly activities during the pandemic were quite tiring due to the increase in the number of activities. In addition, the student activities outside the campus are not effective in supporting their weekly activities as students. This is partly because of feeling bored and disturbed by other activities. Then there was a polarization of student activities during the pandemic, which can increase activity includes: sports, independent learning, running hobbies, and taking care of the house, and several decrease activities namely: socializing, performing arts, taking care of themselves, resting, watching, medical treatment, and weekly worship. This research can contribute to finding out the learning problems of students in their hometowns during the pandemic.